KNOWLEDGE MANAGEMENT SYSTEM DESIGN AT HUMAN RESOURCES DIVISION - Yanti, Yanti; Moniaga, Jurike V (CommIT (Communication and Information Technology) Journal, 2009)
The Human Resources Division of a company is a vital division. Most of the time, they perform their work manually, and therefore creating limitations to their capacity. The knowledge contained is very important for human resources development and subsequently for developing the company. In order to manage this knowledge well, the company shall require a knowledge management system. This knowledge management system would be a solution to be used for the company to manage all knowledge contained in that particular division. Phases in designing knowledge managements starts from analyzing knowledge sources of the company, knowledge identification and definition, and determining knowledge goals. Knowledge management systems contain many functions such as collecting, recording and managing the knowledge and sharing this to all related employees easily. The company may also use knowledge management systems to share and inform employees regarding updates of information, news and/or activity regarding the employees themselves. Information from knowledge management systems may also be used by employees to monitor their performance and thereby increasing it. Knowledge management systems may also help employees in their learning activities.Keywords: knowledge management, human resources, employee